1998
DOI: 10.1074/jbc.273.18.10819
|View full text |Cite
|
Sign up to set email alerts
|

The Peptidyl-prolyl Isomerase Domain of the CyP-40 Cyclophilin Homolog Cpr7 Is Not Required to Support Growth or Glucocorticoid Receptor Activity in Saccharomyces cerevisiae

Abstract: CyP-40 cyclophilins are found in association with molecular chaperone Hsp90⅐steroid receptor complexes. The amino-terminal portion of these cyclophilins harbors the characteristic peptidyl-prolyl isomerase (PPIase) domain, whereas three copies of the tetratricopeptide (TPR) motif, a structure shown to be involved in protein-protein interactions, and a putative calmodulinbinding domain are located in the carboxyl-terminal half of the protein. The TPR domains mediate binding to Hsp90, but a requirement for the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 43 publications
2
54
0
Order By: Relevance
“…We established that sequences outside the PPIase domain are responsible for Cpr7 function. Cpr7-R64A, which alters a residue predicted to be required for catalytic activity (Duina et al 1998b), was able to support viability in cpr7hsc82hsp82 cells expressing hsp82D211-264 (not shown). The chimeric constructs as well as the isolated TPR domain (amino acids 193-393) that supported Cpr7 functions included the TPR domain as well as a linker region postulated to be important for chaperone activity (Mok et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We established that sequences outside the PPIase domain are responsible for Cpr7 function. Cpr7-R64A, which alters a residue predicted to be required for catalytic activity (Duina et al 1998b), was able to support viability in cpr7hsc82hsp82 cells expressing hsp82D211-264 (not shown). The chimeric constructs as well as the isolated TPR domain (amino acids 193-393) that supported Cpr7 functions included the TPR domain as well as a linker region postulated to be important for chaperone activity (Mok et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cpr6 and Cpr7 contain two main domains: an amino-terminal PPIase domain and a carboxy-terminal TPR domain. The PPIase domain of Cpr7 is dispensable for growth (Duina et al 1998b). We made chimeras in which the PPIase domains were swapped, creating Cpr6 PPIase domain/Cpr7 TPR domain (6PPI/7TPR) and Cpr7 PPIase domain/Cpr6 TPR domain (7PPI/6TPR).…”
Section: Tpr Domain Of Cpr7 Specifies Its In Vivo Functionsmentioning
confidence: 99%
“…This results in an increasing amount of reactivatable intermediates of CS. In vivo the deletion of Cpr7 led to a decrease of steroid hormone receptor activation that could not be rescued by overexpression of Cpr6 (32,45). Additionally, it was shown that the PPIase domain of Cpr7 is dispensable for the activation of steroid hormone receptors (32).…”
Section: Catalytic Activity Of the Large Immunophilins In The Accelermentioning
confidence: 99%
“…Depletion of Cpr7 led to a growth defect that could not be rescued by the overexpression of Cpr6 (28,30). In vitro it was shown that Cpr6 is able to catalyze the isomerization of Xaa-Pro peptide bonds (29,31), whereas Cpr7 is assumed to be inactive (32). Here we analyzed and compared the function and stability of Cpr6 and Cpr7.…”
Section: Ppiasesmentioning
confidence: 99%
“…A large body of evidence suggests that the PPIase activity of immunophilins is responsible for various functions (16,46,47). However, the controversy regarding the chaperone function of small immunophilins has yet to be fully settled (18,20,48).…”
Section: And References Therein)mentioning
confidence: 99%